Recreational sandboxes for children and dogs can be a source of epidemic ribotypes of Clostridium difficile. (7th July 2017) - Orden, Cristina; Neila, Carlos; Blanco, José L.; Álvarez‐Pérez, Sergio; Harmanus, Celine; Kuijper, Ed J.; García, Marta E.
Summary: Different studies have suggested that the sand of public playgrounds could have a role in the transmission of infections, particularly in children. Furthermore, free access of pets and other animals to the playgrounds might increase such a risk. We studied the presence of Clostridium difficile in 20 pairs of sandboxes for children and dogs located in different playgrounds within the Madrid region (Spain). Clostridium difficile isolation was performed by enrichment and selective culture procedures. The genetic (ribotype and amplified fragment length polymorphism [AFLP]) diversity and antibiotic susceptibility of isolates was also studied. Overall, 52.5% (21/40) of samples were positive for the presence of C. difficile . Eight of the 20 available isolates belonged to the toxigenic ribotypes 014 ( n = 5) and 106 ( n = 2), both regarded as epidemic, and CD047 ( n = 1). The other 12 isolates were non‐toxigenic, and belonged to ribotypes 009 ( n = 5), 039 ( n = 4), and 067, 151 and CD048 (one isolate each). Nevertheless, all isolates (even those of a same ribotype) were classified into different AFLP genotypes indicating non‐relatedness. In conclusion, our results revealed the presence of epidemic ribotypes of C. difficile in children's and dog's sandboxes located nearby, which constitutes a major health risk.